Pediatric polysomnography-flagging etiologies and impact on the clinical timeline - Rani, Seema; Schanz, John; Chauhan, Kapil; Kolb, August; Gatta, Victoria; Strang, Abigail; Chidekel, Aaron C. (Frontiers in Sleep, 2024)
IntroductionBackground/Objective: There is a paucity of literature regarding "flagging" abnormal sleep studies for expedited review. This single center retrospective analysis (n=266) of flagged polysomnography studies from 2019-2022 aimed to investigate flagging and its impact on clinical timeline.Methods: Two-hundred and sixty-six flagged polysomnography studies from 2019-2022 were retrospectively reviewed.Results: Flagged study etiologies included repetitive brief oxygen desaturations (46.6%), sustained desaturations (32.3%), sustained hypercapnia (5.6%), or other concerning events (15.5%). MedianThe time frombetween a flagged study to scoring a finalized report finalization, medical intervention, orand surgical intervention wereas 0 (2) days, 2 (3) days, 5 (11.25) days, and 44 (73) 4.29 ± 6.01, 26.6 ± 93.0 and 78.2 ± 105 days, respectively. Patients with apnea-hypopnea index >30 had less time between a flagged study and surgical intervention (65.3 ± 96.7 days vs 112 ± 119 days, P=0.044).As anticipated, the time to surgical intervention was longer than medical intervention. Patients with higher disease severity experienced quicker scoring, report finalization, and surgical intervention.